USULAN PENINGKATAN KUALITAS PRODUK PLASTIK DENGAN FISHBONE ANALYSIS DI PT.XYZ - Fanny Nurul Amalia; Wawan Kurniawan; Anik Nur Habyba (Universitas Nusa Cendana, 2021)
Quality is something that must be considered by every company when carrying out the production process in order to get results that are in accordance with standards. PT. XYZ is a company engaged in manufacturing which produces several types of plastics. One type of plastic that is produced by the company and often used by the public is HD plastic in the form of a plastic bag used for shopping. After conducting the research, the product defect in this type of plastic exceeds the defect standard that has been set at 3%. So this research is done using the fishbone analysis method which is used to analyze the factors that affect the quality of plastic bag products. The steps in solving this problem are using CTQ to identify defects in a product. Then do the DPMO and Sigma Level calculations. After that, identify the cause of the problem with the disability that occurs. This problem can be solved using the FMEA method to find out what problems will be solved first. Keywords: Fishbone Analysis, FMEA, DPMO, Sigma Level